Implementing copyright protection policy in digital transformation at the Information and Library Center of University of Transport Ho Chi Minh City - Le , Thị Lệ; Phan, Quốc Cường; Nguyen , Thị Thoa; Le , Văn Cường (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
Copyright is a particularly important aspect regulated by Intellectual Property Law. In the current era of rapid digital transformation, the issue of copyright enforcement has become more pressing than ever. The challenge lies in ensuring compliance with the law while protecting the interests of the authors (or copyright holders) and fulfilling the library's role in disseminating knowledge and helping readers access information. Based on a comparison of the current state of copyright enforcement at the Information and Library Centers of various universities, the authors have proposed a set of solutions to enhance the effectiveness of copyright enforcement at the Information and Library Center of University of Transport Ho Chi Minh City.